Seismic performance of wide flange steel beams partly covered by side plates. (September 2018) - Chen, Cheng-Cheng; Erwin,; Salim, Charles Julius; Tiara, Rudy
Abstract: In this study, the seismic performance of wide flange steel beams partly covered by side plates was investigated experimentally and analytically. The beams investigated were laterally supported at top flange but not at bottom flange. Multiple cases were tested including beams with and without side plates, and the results showed that the beams with side plates showed acceptable performance in terms of strength, ductility, and hysteresis behavior. The lateral torsional buckling was suppressed in beams with side plates. A finite-element model was established and validated using the test results. A parametric study was conducted, which revealed that the lengths of the side plates played an important role in determining the performance of the beams. The side plate length required to achieve the desired performance depended on the strength of the side plate used, beam slenderness ratio, and beam section dimensions such as beam depth-to-width ratio and width-to-thickness ratio of the flanges and web. A design guideline for beams partly covered with side plates was proposed based on the results of the parametric study. The proposed equation to calculate the required side plate length provides a result that is precise enough compared to the analytical result with slight conservatism.